The Temporal Windows of Glycemic Injury: Association of Early and Late First-Week Hyperglycemia with Retinopathy of Prematurity in Low-Birth-Weight Infants - Dharmi Lestari, Ni Putu; I Wayan Eka Sutyawan; Putu Junara Putra; I Gde Raka Widiana; Siska; Putu Yuliawati (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Retinopathy of prematurity (ROP) is a leading cause of childhood blindness, driven by aberrant retinal vascular development in preterm infants. While hyperglycemia is a recognized risk factor, its impact may vary depending on its timing relative to the biphasic pathogenesis of ROP. This study aimed to generate a hypothesis regarding the differential association of hyperglycemia on postnatal day 1 versus day 7 with the incidence of ROP in a high-risk neonatal population. Methods: We conducted a retrospective, cross-sectional, hypothesis-generating study at Prof. Dr. I.G.N.G. Ngoerah General Hospital. Medical records of 68 preterm (<37 weeks gestation) and low-birth-weight (<2500 grams) infants who underwent ROP screening were reviewed. The exposures of interest were hyperglycemia (blood glucose >125 mg/dL) on postnatal day 1 (D1) and day 7 (D7). The primary outcome was the diagnosis of any stage of ROP. Statistical analysis involved Chi-square tests and exploratory multivariate logistic regression to adjust for select confounders. Results: Of the 68 infants included (mean gestational age 30.5 ± 2.2 weeks, mean birth weight 1447.5 ± 373.0 grams), 11 (16.2%) were diagnosed with ROP. Hyperglycemia was present in 29.4% of infants on D1 and 13.2% on D7. In logistic regression analysis, a strong statistical association was observed between hyperglycemia and ROP for both D1 (Adjusted Odds Ratio [AOR] = 55.7; 95% Confidence Interval [CI]: 5.1–611.0; p=0.001) and D7 (AOR = 74.5; 95% CI: 9.0–613.4; p<0.001). However, the profoundly wide confidence intervals indicate significant statistical instability and imprecision. Conclusion: This study found a strong, albeit statistically imprecise, association between hyperglycemia on both the first and seventh day of life and the incidence of ROP. These findings support the hypothesis that the timing of glycemic dysregulation may be critical, potentially impacting different phases of ROP pathogenesis. The results, while preliminary, underscore the need for larger, prospective studies to confirm these associations and elucidate the role of glycemic control in ROP prevention.